Nosewitness Identification: Effects of Lineup Size and Retention Interval - Alho, Laura; Soares, Sandra C.; Costa, Liliana P.; Pinto, Elisa; Ferreira, Jacqueline H. T.; Sorjonen, Kimmo; Silva, Carlos F.; Olsson, Mats J. (Frontiers in Psychology, 2016)
Although canine identification of body odor (BO) has been widely used as forensic evidence, the concept of nosewitness identification by human observers was only recently put to the test. The results indicated that BOs associated with male characters in authentic crime videos could later be identified in BO lineup tests well above chance. To further evaluate nosewitness memory, we assessed the effects of lineup size (Experiment 1) and retention interval (Experiment 2), using a forced-choice memory test. The results showed that nosewitness identification works for all lineup sizes (3, 5 and 8 BOs), but that larger lineups compromise identification performance in similarity to observations from eye- and earwitness studies. Also in line with previous eye- and earwitness studies, but in disagreement with some studies on odor memory, Experiment 2 showed significant forgetting between shorter retention intervals (15 minutes) and longer retention intervals (1-week) using lineups of 5 BOs. Altogether this study shows that identification of body odor in a forensic setting is possible and has limits and characteristics in line with witness identification through other sensory modalities.